Aims, design and preliminary findings of the Hellenic National Nutrition and Health Survey (HNNHS). - Magriplis, Emmanuella.; Dimakopoulos, Ioannis.; Karageorgou, Dimitra. (Tufts University. Tisch Library., 2019)
Keywords: Diet, Public health, Nutrition survey/ methods, Cross-sectional study, Greece.; Background: The aim of the Hellenic National Nutrition and Health Survey was to assess nutritional intake, health status and various behaviors in a representative sample of the Greek population.; Springer Open.